Contention For the Right to Information: Hacktivism as A Social Movement - Elif Kara (Yeni Medya)
Social movements have evolved significantly over time, adapting to historical developments and conditions. Initially perceived as aggressive and aimless, they have transformed into more organised forms, particularly in response to industrialisation. Post-World War II and the Cold War era witnessed a diversification of movements, encompassing issues like women's rights, identity, and the environment. The "right to information" concept has emerged as a modern element, emphasising freedom and accessibility of knowledge. Technological advancements have further reshaped movements, with hacktivism emerging as a modern form, leveraging information to influence politics. The Internet has become integral to social movements, facilitating communication, governance, and activism breaching geographical limitations. However, contrary to the general literature on the digitalisation of social movements, this article asserts that Hacktivism contending on the idea that information is public property and must be free, is a new social movement by itself. It argues that hacktivism is a modern social movement incorporating politically charged hacking into the social movement repertoire and contending for the right to information, demanding more inclusion in political processes and a new societal order. To acknowledge this the article demonstrates the hallmarks of Anonymous and RedHack, two hacktivist groups with different organisational structures and ideological underpinnings and, provides a comparative analysis anticipating that it will avail on political sciences.